Decommissioning of a Lignite Mine Combined with the Development of a Pumped-Storage Power Plant: A Preliminary Feasibility Assessment - Naworyta, Wojciech; Sikora, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This publication addresses the potential construction of a pumped-storage power plant (PSP) in post-lignite mining areas.The Turów mine, located in the Bogatynia commune in southwestern Poland, was selected as a case study. Several design variants for the upper reservoir, situated on the former external mine dump, were analyzed. Several design variants for the upper reservoir, situated on the former external mine dump, were analyzed. Based on data from existing Polish PSP facilities, the potential capacity of the Turów PSP was estimated depending on the selected reservoir configuration.
Keywords: lignite mine; mine decommissioning; pumped-storage power plant; energy storage; external dump; renewable energy